Human Resource Competencies, Information Technology Utilization, and MSME Performance: Evidence from an Emerging Regional Economy - Trisno Wibowo. K; Muliyana Saidi; Rabia H Maudjik; Irmansyah Tija (Vifada Management and Digital Business, 2026)
This study aims to examine the effects of human resource competency and information technology utilisation on the performance of Usaha Mikro, Kecil, dan Menengah (MSME) in Banggai Regency. A quantitative approach employing an explanatory research design was adopted. The study population comprised MSME owners and managers in Banggai Regency, and a purposive sample of 100 respondents was selected. Data were collected through a structured questionnaire on a five-point Likert scale and analysed using multiple linear regression in IBM SPSS Statistics. The analytical procedures included descriptive statistics, validity and reliability testing, classical assumption testing, multiple linear regression, t-test, F-test, and coefficient of determination (R²) analysis. The findings indicate that human resource competency has a positive and statistically significant effect on MSME performance, with a calculated t-value of 4.982 and a significance level of 0.000. Information technology utilisation also has a positive and statistically significant effect on MSME performance, with a calculated t-value of 5.617 and a significance level of 0.000. Furthermore, the simultaneous test indicates that both variables jointly have a significant effect on MSME performance, as indicated by an F-value of 58.742 and a significance level of 0.000. The coefficient of determination (R²) of 0.549 indicates that human resource competency and information technology utilisation jointly explain 54.9% of the variance in MSME performance. In comparison, the remaining 45.1% is attributable to other factors beyond the scope of the research model. These findings suggest that strengthening the competencies of MSME owners and managers, supported by the effective utilisation of information technology, plays a crucial role in enhancing the performance and competitiveness of Usaha Mikro, Kecil, dan Menengah (MSME) in Banggai Regency.